Age-Separated RBCs Show Changes in Oxygen Carrying Capacity and Rigidity During Hypothermic Storage - Mykhailova, Olga O.; Li, Wenhui; Acker, Jason P. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 163.